Pengaruh ROE Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Jakarta Islamic Index (JII) Periode 2019-2021 - Mutiara Praptasari; Daz Vholasky Anggraini; Theysa Sahlani Pratiwi (CV Edujavare Publishing, 2024)
The purpose of this study is to analyze the effect of ROE on company value in the JII group for the 2019-2021 period. Using a quantitative approach to analyze the relationship between ROE and company value as measured by the PER in companies in the JII for the 2019-2021 period. The analysis techniques used include multiple linear regression tests, t-tests, coefficient of determination (R²) tests, and correlation tests to measure the strength of the relationship between variables. The results show that ROE has a significant and positive effect on company value, with most of the PER variability explained by ROE. The results of the analysis show that ROE has a significant and positive effect on company value as measured by PER. Companies with high ROE, such as Unilever Indonesia and Indofood CBP, have high PERs, reflecting investor confidence in the prospect of profit growth. Conversely, companies with lower ROEs such as Vale Indonesia have lower PERs, indicating a more cautious market view. Although ROE has a strong influence, other factors such as macroeconomic conditions, industry prospects, and sharia compliance also affect company value.